3 - Déterminants de la compétitivité financière des P. M. E. Sénégalaises - Sall, Mahmoudou Bocar (Africa Development, 2021)
The purpose of this study is to give a better perception of the effective aspect of financial competitiveness among medium sized companies in Senegal. It presents the results of a hypothesis test on basic variables which are likely to be incidental on companies’ behaviour, in terms of competitiveness. We have worked on a sample of 407 companies from 1998 to 2006, using econometric models of data panels. The results show that the level of competitiveness positively linked to labour (payroll costs) or assets variables vary in accord- ance with the very size or the field of activity of the medium sized company.